The last man on earth - Swanson, Logan, 1926-; Leicester, William F.; Lippert, Robert L.; Salkow, Sidney, 1909-2000.; Price, Vincent, 1911-1993.; Bettoia, Franca; Danieli, Emma.; Rossi-Stuart, Giacomo, 1931-1994.; Matheson, Richard, 1926- (Del Mar, Calif. : Genius Entertainment, 1964)
Thinking himself the only person alive after a plague that killed his wife and child, a scientist fights a nightly battle with what appear to be vampires, trying to break into his house.
Widescreen presentation; digitally remastered, sound enhanced.
"Golden movie classics"--Disc label.
Originally produced as a motion picture in 1964.
Based on the novel, I am legend / by Richard Matheson.
Director of photography, Franco delli Colli ; editor, Gene Ruggiero ; music, Paul Sawtell, Bert Shefter.
Vincent Price, Franca Bettoia, Emma Danieli, Giacomo Rossi -Stuart.
Keywords: Vampires -- Drama; Plague -- Drama; Vampire films; Feature films; Horror films